Development of Comic in Qiroah Learning Introduction Material for VII Grade at Mts Muallimin NW Pancor / Pengembangan Media Komik Pada Pembelajaran Qiroah Materi Perkenalan Kelas VII Mts Muallimin NW Pancor - Hidayat Agusvian; Asep Sopian; Nunung Nursyamsiah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
Learning the Arabic language at Mts Muallimin NW pancor using the standard textbooks without any improvisation in presenting Arabic language learning materials, the author tries to develop Arabic language learning media with comic media aimed at presenting new media that are more attractive to students Mts Muallimin NW Pancor, the methodology used in this research is the research method of development R&D ( Research and Development) Borg and Gell. One media expert lecturer and one material expert lecturer reviewed product feasibility and responded by 30 students of grade VII MTS Muallimin NW Pancor; the instrument in this research is a questionnaire to see the quality of products and students' responses media. The assessment results from both experts obtained a value of 52 for the assessment of material experts in the range of 44.16 < X_(<) 54.48, which means comic media can be said to be valid and 65 for the assessment of media experts and is in the range of 54.36 < X_(<) 67.08. It means comic media can be said to be valid. Moreover, the questionnaire's response with respondents who answered 'Yes' in the school MTS Muallimin NW Pancor was about 94.8% compared to students who answered "no," namely 5.2%. The comic media product developed is worthy of being used to learn the Arabic language from the research. Keywords: Development, Arabic language learning, Comic media. Abstrak Pembelajaran bahasa Arab di MTS Muallimin Nw pancor menggunakan buku pelajaran yang biasa tanpa ada imvropisasi dalam menyajikan materi pembelajaran bahasa Arab, penulis mencoba untuk mengembangkan media pembelajaran bahasa Arab dengan media komik yang bertujuan untuk memeberikan media baru yang lebih menarik bagi siswa Mts muallimin nw Pancor, metodologi yang digunakan dalam penelitian ini adalah metode penelitian pengembangan R&D ( Research And Depelopement) Borg and Gell. Kelayakan produk ditinjau oleh satu dosen ahli media, dan satu dosen ahli materi,. Dan direspon oleh 30 peserta didik kelas VII Mts Muallimin NW Pancor, dalam penelitian ini menggunakan instrument berupa angket untuk melihat kualitas produk dan respon siswa terhadap media. Hasil penilaian dari kedua ahli diperoleh nilai 52 untuk penilaian ahli materi yang berada pada rentang 44,16 < X 54,48 yang berarti media komik dapat dikatakan valid dan 65 untuk penilian ahli media dan berada pada rentang 54,36 < X 67,08. Yang berarti media komik dapat dikatakan valid. Dan respon angket siswa dengan hasil responden yang menjawab ‘Ya’ di sekolah Mts Muallimin NW Pancor, sekitar 94,8% dibandingkan dengan siswa yang menjawab “tidak”yaitu 5,2%.dari hasi penelitian tersebut maka produk media komik yang dikembangkan layak untuk dijadikan sebagai media pembelajaran bahasa Arab . Kata Kunci: Pengembangan, Pembelajaran Bahasa Arab, Media Komik.